Differential compartmentalization of memory B cells versus plasma cells in salmonid fish. Issue 2 (14th February 2013) - Ma, Cuiyan; Ye, Jianmin; Kaattari, Stephen L.
<x xml:space="preserve">Abstract</x> The disposition of teleost memory and plasma cells (PCs) has essentially been un‐explored. As the organization of the teleost immune system differs significantly from that of mammals (i.e. no bone marrow or lymph nodes, hematopoietic anterior kidney), this disposition could be essential in understanding how comparable functions are achieved. To address this question, the primary and secondary antibody‐secreting cell, B memory cell, and antibody responses to T‐independent and T‐dependent antigens were analyzed in trout. Although the TI and TD antibody responses did not differ substantively from one another, the secondary responses to both were significantly prolonged compared with the primary responses. Logarithmic increases in titer and affinity were achieved for both antigens during the primary, with only modest increases during the secondary response. Antibody‐secreting cells, both PCs and plasmablasts, quantitatively paralleled antibody production, with antibody‐secreting cells skewing to the hematopoietic anterior kidney for both antigens. However, the enhanced antigen‐inducible response of immune fish (indicative of the memory pool) skewed to the peripheral blood and spleen. This pattern of memory versus PC disposition parallels that observed in mammals even though the organization of the respective immune systems differs considerably.